Real-Time 3-Dimensional Ultrasound-Assisted Infraclavicular Brachial Plexus Catheter Placement: Implications of a New Technology. (29th April 2010) - Clendenen, Steven R.; Robards, Christopher B.; Clendenen, Nathan J.; Freidenstein, James E.; Greengrass, Roy A.
Abstract : Background . There are a variety of techniques for targeting placement of an infraclavicular blockade; these include eliciting paresthesias, nerve stimulation, and 2-dimensional (2D) ultrasound (US) guidance. Current 2D US allows direct visualization of a "flat" image of the advancing needle and neurovascular structures but without the ability to extensively analyze multidimensional data and allow for real-time manipulation. Three-dimensional (3D) ultrasonography has gained popularity and usefulness in many clinical specialties such as obstetrics and cardiology. We describe some of the potential clinical applications of 3D US in regional anesthesia. Methods . This case represents an infraclavicular catheter placement facilitated by 3D US, which demonstrates 360-degree spatial relationships of the entire anatomic region. Results . The block needle, peripheral nerve catheter, and local anesthetic diffusion were observed in multiple planes of view without manipulation of the US probe. Conclusion . Advantages of 3D US may include the ability to confirm correct needle and catheter placement prior to the injection of local anesthetic. The spread of local anesthetic along the length of the nerve can be easily observed while manipulating the 3D images in real-time by simply rotating the trackball on the US machine to provide additional information that cannot be identified with 2D US alone.